Aplikacation of Learning Start with a Question (LSQ) Strategy in Improving the Activeness of Questioning and Learning Outcomes of Islamic Religious Education - Mawarwati, Mawarwati; Kadir, St. Fatimah; Rahmawati, Rahmawati (IAIN KENDARI, 2025)
Through the use of the Learning Start with a Question technique, this research seeks to improve the fifth-grade students' active question-asking behavior and learning results. Classroom Action study (CAR), which includes planning, implementing, observing, and reflecting processes, is the study methodology employed. At SD Negeri 83 Kendari, this study was carried out. For the school year 2021–2022, 29 pupils in class V served as the study's subjects. Both qualitative and quantitative data analysis methods are used. Data from observations of instructor and student activities are used in qualitative data analysis, whereas data on the results of student learning are used in quantitative data analysis. In cycle I, not all teacher and student learning activities were in line with the Learning Start with a Question learning steps, according to the findings of observations, whereas in cycle II, the Learning Start With a Question learning steps were appropriate and demonstrated a very good category. According to the study cycle's findings, instructor participation was inadequate at the first meeting, with a percentage of 70.6%, and rather excellent at the second meeting, with a percentage of 78.6%. Cycle II received a percentage of 86.6% in the